2019
DOI: 10.1161/strokeaha.118.024460
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends in Race-Ethnic Differences in Do-Not-Resuscitate Orders After Stroke

Abstract: Background and Purpose-Do-not-resuscitate (DNR) orders are common after stroke, though there are limited data on trends over time. We investigated time trends in DNR orders in a community with a large minority population. Methods-Cases of ischemic stroke (IS) or intracerebral hemorrhage (ICH) were identified from the Brain Attack Surveillance in Corpus Christi (BASIC) study from June 2007 through October 2016. Cox proportional hazards models were used to assess time to DNR orders, with an interaction term adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, the direction of the effect remained in favor of better outcomes among MA surrogates, contrary to our original hypothesis. Surrogate decision-making about life-sustaining treatment after stroke is common 1,5 with potential implications for life or death decisions for the patient 17 and potential long-term adverse impact on surrogates 3 and yet been largely understudied in the setting of stroke. These findings from a community-based study examining stroke surrogate decision-making and surrogate-reported outcomes may help to draw attention to the importance of studying the effects of stroke on the entire family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the direction of the effect remained in favor of better outcomes among MA surrogates, contrary to our original hypothesis. Surrogate decision-making about life-sustaining treatment after stroke is common 1,5 with potential implications for life or death decisions for the patient 17 and potential long-term adverse impact on surrogates 3 and yet been largely understudied in the setting of stroke. These findings from a community-based study examining stroke surrogate decision-making and surrogate-reported outcomes may help to draw attention to the importance of studying the effects of stroke on the entire family.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have also shown differences in the frequency of decisions to limit life-sustaining treatments by race and ethnicity. [4][5][6] We have shown that Mexican American (MA) patients are less likely than non-Hispanic White (NHW) patients to have early do-not-resuscitate (DNR) orders after stroke. 5 Despite longstanding documentation of differences in treatment patterns by race and ethnicity, reasons underlying these differences remain elusive.…”
mentioning
confidence: 99%
“…An NIS study of individuals with hemorrhagic strokes showed that White patients are more likely to receive DNR or palliative orders 30 . A study in 2006-2014 showed that DNR orders in AIS were less likely to be given to Mexican Americans and Black individuals within 24 hours, but no difference was found afterwards 31 . Another study reported lower utilization of palliative care in 2007-2011 in non-White minority patients in all hospital strata by the proportion of the non-White patients served, as well as in all race/ethnicities in hospitals predominantly serving the non-White patients 32 .…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous research concerning DNR orders in the inpatient setting suggests that racial and ethnic differences have not changed over time. 13,14 However, there is increasing interest in understanding variation in medical decision-making by race and ethnicity. Cardiopulmonary resuscitation (CPR) preferences captured in POLST over time have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…But, fewer Black and Hispanic nursing home residents, compared to White residents, have POLST forms containing DNR orders 12 . Previous research concerning DNR orders in the inpatient setting suggests that racial and ethnic differences have not changed over time 13,14 . However, there is increasing interest in understanding variation in medical decision‐making by race and ethnicity.…”
Section: Introductionmentioning
confidence: 99%